Abnormal Interactions of the Salience Network, Central Executive Network, and Default-Mode Network in Patients With Different Cognitive Impairment Loads Caused by Leukoaraiosis - Chen, Hongyan; Li, Yuexiu; Liu, Qi; Shi, Qingli; Wang, Jingfang; Shen, Huicong; Chen, Xuzhu; Ma, Jun; Ai, Lin; Zhang, Yu Mei (Frontiers in Neural Circuits, 2019)
Leukoaraiosis (LA) is considered to be associated with cognitive impairment in the older people. This alteration can be reflected in functional connectivity (FC) based on resting-state functional MRI (rs-fMRI). In this study, we used the triple brain network model to investigate altered changes in FC for LA with different cognitive impairment loads determined by the Mini Mental State Exam (MMSE) and Clinical Dementia Rating (CDR). Eighty-three subjects were divided into four groups based on their clinical diagnosis: the LA-normal cognition group (LA-NC) (n=14, 6 males), LA with mild cognitive impairment (LA-MCI) group (n=27, 13 males), LA with vascular dementia (LA-VD) group (n=12, 6 males) and matched healthy controls (HC) (n=30, 11 males). The triple brain network model includes the default-mode network (DMN), salience networks (SN) and the central executive network (CEN), which were extracted with independent components analysis (ICA) and region of interest (ROI) based analysis using the REST toolbox. LA group presented decreased FC for all these three brain networks, compared with matched healthy controls. For inter-brain network analysis, there were decreased negative FC between the SN and DMN in LA group. While there were enhanced inter-brain network FC between the SN and CEN as well as within the SN. The decrease of FC between SN and DMN may reflect the damage mechanism of cognitive impairment of LA, which can compensate with the enhanced inter-brain network between SN and CEN and intra-brain network FC within the SN.